The Analysis of Gender Roles Divisioan In Dual Career Families - Tiffany, Kenithasia Tyas; Sartika, Diana Dewi; Lidya, Eva (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This research focuses on discussing the division of productive, reproductive, and social gender roles in dual-career families in the Inderalaya Raya sub-district. The division of roles in a dual-career family certainly has its own difficulties and challenges, such as the division of roles involving children, work, household, and time. The purpose of this study is to identify the division of roles between husbands and wives who work in deciding the division of roles in family life. The research method used is descriptive-qualitative with a narrative research strategy. This study used role theory, and data was obtained from six pairs of husband and wife informants and three child informants through observation, in-depth interviews, and documentation. The results of the study show that the husband and wife have agreed on a joint decision to balance work responsibilities in the formal sector and household affairs, which can be in the form of full direct involvement of the husband and wife or assistance from a third party in carrying out the reproductive role. The multiple roles that are carried out will experience role conflict if there are two or more pressures that occur simultaneously. Role theory states that role strain and role failure carried out by someone will also lead to conflict and can even lead to gender inequality. However, workers and parents who carry out their roles well are made role models by the child